Semen quality and sperm DNA methylation in relation to long-term exposure to air pollution in fertile men: A cross-sectional study. (1st May 2022) - Cheng, Yuting; Tang, Qiuqin; Lu, Yiwen; Li, Mei; Zhou, Yijie; Wu, Peihao; Li, Jinhui; Pan, Feng; Han, Xiumei; Chen, Minjian; Lu, Chuncheng; Wang, Xinru; et al.
Abstract: Some studies have examined the association between air pollution and semen quality. While it is less of evidence on the sperm quality after long-term air pollution exposure, especially the co-exposure of different air pollution components. Additionally, the role of DNA methylation in it hasn't been confirmed. This study aimed to investigate whether long-term exposure to air pollution was associated with semen quality, as well as to explore the effect of sperm DNA methylation in such association. From 2014 to 2016, 1607 fertile men were enrolled to evaluate 14 parameters of semen quality. Exposure window was defined as one-year before semen sampling. Multivariable linear regression and weighted quantile sum (WQS) regression model were used to investigate the association between six air pollutants co-exposure and semen quality. Sensitivity analysis regarding at the normal semen quality group was also conducted. Semen samples were randomly selected from 200 participants to detect the genomic 5-methylcytosine (5 mC) and 5-hydroxymethylcytosine (5-hmC) levels in sperm. In the total population, PM10, PM2.5, SO2, and NO2 were negatively associated with sperm total motility (PM10 : β = −2.67, P  = 0.009; PM2.5 : β = −2.86, P  = 0.004; SO2 : β = −2.32, P  = 0.011; NO2 : β = −2.21, P  = 0.012). Results of the normal semen quality group were consistent with those from the whole population. WQS regression results indicated significant decreasing sperm total motility after the co-exposure of the six air pollutants (β = −1.64, P  = 0.003) in whole participants. Wherein, PM10 accounted for largest proportion (43.4%). The 5-hmC level was positively associated with PM10 exposure (β = 0.002, P  < 0.001). Long-term exposure to PM10, PM2.5, SO2, and NO2, as well as co-exposure to six air pollutants, reduced semen quality in fertile men. As the most significant contributor of air pollutant, PM10 exposure decreased sperm DNA methylation. Graphical abstract: Image 1 Highlights: Long-term exposure to air pollution associated with decreased sperm total motility. Co-exposure to six air pollutants reduced semen quality in fertile men. Long-term exposure to air pollution affected DNA methylation 5-hmC levels in sperm.